PROFITABILITAS MERUPAKAN SINYAL PENTING YANG MENJELASKAN NILAI PERUSAHAAN - Felista Mardiana Tae Nahak; Efraim Ferdinan Giri (LPPM STIE YKPN Yogyakarta, 2023)
This research expands previous research which has examined the factors that influence company value on the Indonesian Stock Exchange. Purpose: This research wants to show that the elements of financial reports provide signals for investors in making investment decisions. This research aims to examine the influence of profitability, solvency and liquidity on company value. Method: This research used 120 samples from 40 companies listed in the LQ45 company category during 2020- 2022. Profitability is measured by the ROA ratio, solvency is measured by the Debt Ratio (DR), and liquidity is measured by the Current Ratio (CR). Analysis: the research model was tested using multiple linear regression. Results and Discussion: Profitability has a positive and significant effect on company value, while the solvency and liquidity variables have an insignificant effect on company value. The results of this research imply that company profitability is an important signal for investors in managing investments in the capital market and for determining company value.